Dementia with Lewy bodies: a clinical case study on the differential diagnosis of atypical parkinsonism - Petrashevska, Yaroslava; Shkodina, Anastasia; Delva, Mykhailo (The Ukrainian Scientific Medical Youth Journal, 2026)
Introduction. Parkinsonism and dementia pose a significant challenge to modern society, as medicine can only offer symptomatic treatment, which may be more effective when diagnosed at the early stages of progression. To date, successfully performing a differential diagnosis of atypical parkinsonism syndrome and establishing the correct diagnosis remains a challenging task, particularly given limited diagnostic resources. Aim. The aim of the study was to conduct a differential diagnosis of atypical parkinsonism based on consensus international criteria, using the example of a clinical case of dementia with Lewy bodies, and to demonstrate the diagnostic and therapeutic process using clinical, neuroimaging, electrophysiological and neuropsychological criteria. Materials and methods. We present a clinical case of a 75-year-old patient with atypical parkinsonism. Informed consent for publication has been obtained. The following were performed: neurological examination, neuropsychological testing (Mini-Mental State Examination, Montreal Cognitive Assessment), magnetic resonance imaging of the brain with assessment of atrophy (Global Cortical Atrophy scale), electroencephalography, and a levodopa test. The diagnosis was established in accordance with the criteria of the International Society for Parkinson’s Disease and Movement Disorders, as well as the consensus on Lewy body dementia. The duration of follow-up was 6 months. Results. The efficacy of treatment with cholinesterase inhibitors, anti-Parkinson’s drugs and melatonin was assessed. A stepwise differential diagnosis of atypical parkinsonism was performed. Initially, a diagnosis of multiple system atrophy of the parkinsonian subtype was established on the basis of oligo-bradykinesia, plastic hypertonia, limb ataxia and a poor response to the levodopa test. However, the detection of recurrent episodes of cognitive fluctuations to the level of moderate dementia (MMSE 19–20 points) and persistent visual hallucinations, which are exclusion criteria for multiple system atrophy, led to a revision of the diagnosis. Clinically probable dementia with Lewy bodies was established, presenting with all four core features: cognitive fluctuations, visual hallucinations, clinically probable behavioural disturbances during rapid eye movement (REM) sleep, and parkinsonism. Combination therapy with rivastigmine (3 mg in the morning, 1.5 mg at night), amantadine (100 mg/day), levodopa retard (100/25 mg/day) and melatonin (10 mg) resulted in significant clinical improvement: a reduction in the frequency of cognitive-hallucinatory fluctuations to once every 2–3 months, improved cognitive function (MMSE 22 points), reduced muscle rigidity and restoration of partial self-care. Conclusion. This case presents a classic example of Lewy body dementia with all four diagnostic features, but illustrates the typical difficulties arising from the overlap in the manifestations of synucleinopathies. The early onset of cognitive fluctuations, hallucinations and behavioural disturbances during rapid eye movement sleep, combined with resistant parkinsonism, creates a highly specific pattern of Lewy body dementia, even in the presence of ataxia and autonomic dysfunction.